Use of Genotype MTBDRplus Assay for Diagnosis of Multidrug-Resistant Tuberculosis in Nepal. (13th August 2017) - Maharjan, Elina; Pant, Narayan Dutt; Neupane, Sanjeev; Amatya, Jyoti; Shrestha, Bhawana
Abstract : The main aims of this study were to study the patterns of mutations in rpoB, katG, and inhA genes in Mycobacterium tuberculosis strains isolated from patients from Nepal and to evaluate the performance of genotype MTBDRplus assay, taking conventional drug susceptibility testing as gold standard for diagnosis of MDR-TB. A total of 69 Mycobacterium tuberculosis strains isolated from 73 smear positive sputum samples from patients suspected of suffering from multidrug-resistant tuberculosis were used in our study. The drug susceptibility pattern of Mycobacterium tuberculosis isolated from these sputum specimens was determined by using genotype MTBDRplus assay taking conventional drug susceptibility testing as reference. The sensitivity and specificity of the genotype MTBDRplus assay for the detection of MDR-TB were found to be 88.7% and 100%, respectively. 88.7% of the rifampicin resistant isolates had mutations in rpoB gene. Similarly, 79.7% and 9.4% of isoniazid resistant isolates had mutations in katG and inhA genes, respectively. Genotype MTBDRplus assay was found to be very rapid and highly sensitive and specific method for diagnosis of MDR-TB and will be very helpful for early diagnosis of MDR-TB in high tuberculosis burden countries.